EXPLORING THE RELATIONSHIP BETWEEN WORKPLACE DIVERSITY AND INNOVATION AT WORLD VISION INTERNATIONAL - NIWAHA JOEL (Uganda Christian University, 2024)
The study aimed to explore the relationship between workplace diversity and innovation at World Vision International in Uganda. The research specifically examined how gender diversity, ethnic diversity, and cultural diversity contribute to the organization’s innovation outcomes, including new product development, process improvement, and market performance. A quantitative research design was adopted, using a sample of 50 respondents drawn from the Human Resources department, based on their experience. Data were collected through structured questionnaires, and the analysis was conducted using descriptive statistics, correlation, and regression analysis. The results indicated that workplace diversity has a positive and significant impact on innovation within the organization. Both gender and ethnic diversity were found to significantly contribute to innovation outcomes, with correlation coefficients of 0.60 and 0.68, respectively. The regression analysis revealed that workplace diversity explained 45% of the variance in innovation, with both gender and ethnic diversity being significant predictors. These findings suggest that organizations like World Vision can enhance their innovation capabilities by fostering a diverse and inclusive workforce. The study concludes with recommendations for organizational policies that promote diversity and innovation and identifies areas for further research.
this abstract summarizes a study exploring the relationship between workplace diversity and innovation at World Vision International in Uganda. It focuses on how gender, ethnic, and cultural diversity impact innovation outcomes like product development, process improvement, and market performance. Using a quantitative research design and data from 50 respondents, the analysis (descriptive statistics, correlation, and regression) showed a positive relationship between diversity and innovation. Gender and ethnic diversity were significant contributors, explaining 45% of the variance in innovation. The study suggests promoting diversity to boost innovation and offers recommendations for future research.